Available Energy and Environmental Economics - Zhu, Junpeng; Xu, Xinlong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on the rapid development of the social economy which is accompanied by the continuous growth of energy demand, such as in the heavy industry, agriculture sector, and tourism sector. Meanwhile, large-scale energy consumption in the short term has increased the risk to the energy supply and ecological safety. This has contributed to the exploration and exploitation of energy supply risk management, carbon emission reduction, and renewable energy technological innovation, aiming to solve the bottlenecks in energy and environmental economics. Thus, this book aims to present and disseminate the most recent advances related to the theory, design, modelling, and application of all types of energy and environmental economics.